Late ureteral obstruction in an adult who had STING/Teflon in childhood: Should we expect an epidemic? - Rosenberg, Shilo; Duvdevani, Mordechai; Sfoungaristos, Stavros; Lorber, Amitay; Landau, Ezekiel H.; Pode, Dov; Gofrit, Ofer N.; Hidas, Guy; Duvdevani, Mordechai; Sfoungaristos, Stavros (Canadian Urological Association Journal, 2015)
We present a case of left renal colic in a 25-year-old female patient. She had subureteral injection of Teflon (STING) at the age of 10 due to vesico-ureteral reflux (VUR) disease and recurrent urinary tract infections. Renal colic was the result of late ureteral obstruction due to Teflon-induced periureteral foreign body reaction. To our knowledge, this is the longest interval between STING and ureteral obstruction reported and the first case of delayed ureteral obstruction caused by Teflon. Monitoring the upper tracts of patients after STING should go beyond childhood.